Ad memoriam. Academician Valery Grigorievich Savchenko - S. Yu. Pushkin; A. S. Nikolaeva; I. Ya. Aleksandrova; U. V. Maslikova (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
In memory of academician V.G. Savchenko, who made an invaluable contribution to the development of the program bone marrow transplants both in Russia and in the Samara region.